Integrasi Nilai Islam dalam Pembentukan Karakter Anak Usia Dini: Peran Keluarga dan Strategi Pembiasaan - Alwasit; Yesi Arikarani; Andini; Indah Nurfaizah A’yunin (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study explores the crucial role of parents and the family environment in shaping children's character from an early age, particularly through the integration of Islamic values. Many parents lack an understanding of child psychological development and often underestimate the importance of early education, delegating the responsibility to others. However, early childhood is a critical period for personality and moral development. Using a literature review method, this research emphasizes the necessity of a holistic and continuous character-building approach, involving family education, school, and extracurricular activities. Core Islamic principles tauhid (monotheism), akhlaq (noble character), and obedience serve as the foundation for developing strong moral character. Effective character education combines habituation, instruction, and mentoring, with parental role-modeling as a key factor. Early and consistent character education fosters children who are spiritually intelligent, morally upright, and socially responsible. Instilling positive values within the family and surrounding environment forms the essential groundwork for raising individuals with strong moral integrity and social resilience.